2018
DOI: 10.1016/j.jcs.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Apparent amylase diffusion rates in milled cereal grains determined in vitro: potential relevance to digestion in the small intestine of pigs

Abstract: Starch digestion in grain particles depends on the diffusion of amylase into the particles. Enzyme diffusion rate (EDR) is influenced by grain structure, and may be key in determining the extent of grain digestion in the small intestine. EDR values of sixteen grains (wheat, barley and sorghum) were compared with their ileal digestibility from pigs. Five fractions of each hammer-milled grain were digested in vitro under conditions mimicking monogastric digestion to obtain apparent amylase diffusion coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Until recently, this had only been determined in a few grain samples (Al-Rabadi et al, 2009;Mahasukhonthachat et al, 2010). However, a recent study (Ratanpaul et al, 2018) showed that plotting the inverse of the first-order digestion rate coefficient against the square of particle size ( Figure 1) gave linear plots for all of 16 diverse grain samples, consistent with a surface area-dependent rate-limiting step. The slope of this plot provides the diffusion coefficient for pure diffusion control, but as other surface area-dependent factors cannot be ruled out, we propose to designate this value as an apparent enzyme diffusion coefficient.…”
Section: Recent Developments In Starch Digestion Methods (In Vitro)mentioning
confidence: 88%
See 3 more Smart Citations
“…Until recently, this had only been determined in a few grain samples (Al-Rabadi et al, 2009;Mahasukhonthachat et al, 2010). However, a recent study (Ratanpaul et al, 2018) showed that plotting the inverse of the first-order digestion rate coefficient against the square of particle size ( Figure 1) gave linear plots for all of 16 diverse grain samples, consistent with a surface area-dependent rate-limiting step. The slope of this plot provides the diffusion coefficient for pure diffusion control, but as other surface area-dependent factors cannot be ruled out, we propose to designate this value as an apparent enzyme diffusion coefficient.…”
Section: Recent Developments In Starch Digestion Methods (In Vitro)mentioning
confidence: 88%
“…Smaller particles are digested faster in the SI than larger particles, providing more energy for normal body function and growth. Milled grain particle size has a major impact on starch digestion rate as found from in vitro studies (Al-Rabadi et al, 2009;Mahasukhonthachat et al, 2010;Ratanpaul et al, 2018). Smaller particles lead to a greater extent of growth and feed efficiency in pigs (De Jong et al, 2016;Al-Rabadi et al, 2017).…”
Section: Recent Developments In Starch Digestion Methods (In Vitro)mentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, understanding the kinetics of starch digestion may also be beneficial for enhancing growth performance of pigs. The kinetics of starch digestion has been measured by the amylase diffusion rate, and it appears that formulating diets with sources of starch that have high intrinsic digestibility increases growth performance of nursery pigs [ 328 ]. This enhanced growth performance may be due to the greater digestibility of starch in feed ingredient sources that have greater intrinsic amylase diffusion rates.…”
Section: Nutrient Digestion Kinetics Of Feed Ingredientsmentioning
confidence: 99%